Sosialisasi dan Skrining Bullying sebagai Upaya Pencegahan Gangguan Kesehatan Mental pada Siswa - Rizal Fajri; Feri Catur Yuliani; Putri Kusumawati Priyono (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Bullying in schools, marked by power imbalance, significantly impacts students’ mental health and increases the risk of depression. Preventive efforts through awareness programs and educational interventions are essential to equip adolescents with skills to address and resist bullying. Objective: The purpose of this activity is to provide information to students, guidance counselors, and student affairs administrators about the impact of bullying on students' mental health. Method: This activity began with bullying screening for all students at SMP N 1 Jatinom Klaten. After all students completed the screening, the researchers analyzed the results and consulted and discussed them with the vice principal for student affairs and guidance counselors to determine which students needed education on bullying issues. Following that, the researchers delivered a 45-minute socialization session together with the Vice Principal for Student Affairs, guidance counselors, and 15 students. The material was presented using PowerPoint with a lecture and discussion method for 30 minutes. Result: The results of this activity from the bullying screening showed that 15 students were victims and perpetrators of bullying. For the participants of the socialization, especially the students, they became more aware of the dangers of bullying to a person's mental health. Conclusion: The overall conclusion of this community service activity shows the effectiveness of the educational approach in improving students' understanding of the phenomenon of bullying and its consequences for mental health.